No more blind dates with calcite: Fluid-flow vs. fault-slip along the Očkov thrust, Prague Basin - Roberts, Nick M.W.; Žák, Jiří; Vacek, František; Sláma, Jiří (Di xue qian yuan., 2021)
Dating of fracture-filling calcite with U-Pb geochronology is becoming a rapidly adopted technique for determining the absolute timing of brittle deformation in the upper crust. Slickenfibre calcite is a desirable target, as it precipitates between individual fault slip displacement events, and provides additional kinematic information. Here we present a case study of slickenfibres formed on the Očkov thrust in the Lower Palaezoic Prague Basin, Bohemian Massif, utilising a combination of petrographic and in situ methods. We demonstrate that slickenfibre external textures can be preserved, whilst internally primary textures are removed by fluid infiltration and recrystallization, leading to variable U and Pb mobilisation. One slickenfibre yielded a date of ca. 250 Ma, which we interpret as recording fault slip along the Očkov thrust. Another cross-cutting slickenfibre yielded more scattered U-Pb data, with an imprecise apparent age around ca. 95 Ma. This slickenfibre is recrystallised, destroying the primary textures, and exhibits element mobility. The meaning of this younger apparent age is therefore questionable; whereas it likely reflects Cretaceous U and Pb mobility assisted by fluid-flow along the fault plane, it may not reflect a period of fault slip. Our results demonstrate that slickenfibre-based U-Pb dates do not unequivocally relate to fault motion, and that petrographic and elemental analyses are important requirements for interpreting calcite U-Pb data. [Display omitted] •Imaging, trace elements and U-Pb dating of calcite from the Očkov fault, Prague Basin.•The Očkov fault acted as a location of polyphase post-orogenic intraplate deformation.•Slickenfibre-based U-Pb dates do not unequivocally relate to fault motion.